Supply chain and logistics management concepts, methodologies, tools, and applications (Business Science Reference, an imprint of IGI Global, 2020)
"This book centers on the effective management of risk factors and the implementation of the latest supply management strategies. It also explores the field of digital supply chain optimization and business transformation"--